The process of accumulation wagons at marshalling yards with a firm timetable trains - Svetashev A.A.; Svetasheva N.F. (Научно-технический вестник Брянского государственного университета)
The aim is to study sostavoobrazovaniya in marshalling yards and characterizing its parameters, as well as dependencies that determine these parameters and costs of car-hours of accumulation of wagons with solid graphics. Results: A de-tailed process of accumulation of cars on the train composition, as well as provides features wagons accumulation proc-ess with solid graphics. Practical significance: is a detailed examination of the process of accumulation of cars in view of admission of certain groups of cars that define the cost of wagon-hours to build cars. Their practical application will allow for more accurate and reasonably easy to normalize cars for accumulation, as well as to clarify the method of cal-culating the train formation plan.